AGE DYNAMICS OF EXTERIOR FEATURES OF BULLS OF EARLY MATURING AND FAST GROWING MEAT AND COMBINED BREEDS - Козырь, В С.; Цвигун, О. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The exterior is closely related to the constitutional characteristics of animals. In the conditions of the steppe zone of Ukraine, as in other regions, research is not enough and this work should be continued, since evolutionary changes in the rocks occur constantly. Therefore, our research is relevant. In the experimental farm of the Institute of Grain Crops, 3 groups of bull-calves of specialized meat Hereford, Charolese and combined Simmental breeds were formed (15 animals each). The content was loose, the feeding conditions were the same. Herefords are smaller than Charolais and are inferior to them in all body measurements (height, width, length, depth). However, they are more compact with pronounced meat forms. Although after 18 months of age, the indicators of articles decreased markedly and some obesity was observed, which confirms their early maturity. Gobies were characterized by a harmonious physique, had rounded shapes, and their lateral profile resembled a rectangle, which indicates a potentially high meat productivity. Their head is short and wide, the neck is short and thick, the chest is deep, wide with rounded ribs, but relatively short, the topline is straight and wide, the back is straight, long, wide, the legs are widely spaced, strong, the muscles are magnificently developed, the skin is loose, thick long hair. At the end of the study, the exterior features of Simmental bulls differed in a greater direction from animals of specialized meat breeds in terms of measurements of such items as height at the withers, back and rump, depth and chest girth. However, they were inferior to them in chest width, in the hips, hip joints, sciatic tubercles.